Early fecal microbiota transplantation from high abdominal fat chickens affects recipient cecal microbiome and metabolism - Song, Jiani; Luo, Chaowei; Liu, Zhijie; Liu, Jingshou; Xie, Li; Zhang, Xing; Xie, Zhuojun; Li, Xiangkun; Ma, Zheng; Ding, Jinlong; Li, Hua; Xiang, Hai (Frontiers in Microbiology, 2024)
Abdominal fat deposition (AFD) in chickens is closely related to the gut microecological balance. In this study, the gut microbiota from high-AFD chickens was transplanted into the same strain of 0-dayold chicks via fecal microbiota transplantation (FMT). The FTM from chickens with high AFD had no obvious effects on growth traits, adult body weight, carcass weight, abdominal fat weight, and abdominal fat percentage, but did reduce the coefficient of variation of AFD traits. FMT significantly decreased cecal microbiome richness, changed the microbiota structure, and regulated the biological functions associated with energy metabolism and fat synthesis. Additionally, the cecal metabolite composition and metabolic function of FMT recipient chickens were also significantly altered from those of the controls. Transplantation of high-AFD chicken gut microbiota promoted fatty acid elongation and biosynthesis and reduced the metabolism of vitamins, steroids, and carbohydrates in the cecum. These findings provide insights into the mechanisms by which chicken gut microbiota affect host metabolic profiles and fat deposition.